2017
DOI: 10.1053/j.gastro.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Active Choice and Financial Incentives to Increase Rates of Screening Colonoscopy–A Randomized Controlled Trial

Abstract: Behavioral economic approaches could increase uptake for colorectal cancer screening. We performed a randomized controlled trial of 2245 employees to determine whether an email containing a phone number for scheduling (control), an email with the active choice to opt in or opt out (active choice), or the active choice email plus a $100 incentive (financial incentive) increased colonoscopy completion within 3 months. Higher proportions of participants in the financial incentive group underwent screening (3.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 15 publications
0
54
0
1
Order By: Relevance
“…12 Organizational and leadership alignment on our CRC screening goal has contributed to our ability to double CRC screening rates in the first 5 years of our program. 12 In this issue of Gastroenterology, Mehta et al 13 at the University of Pennsylvania performed a randomized trial among 2245 employees of their institution comparing an email outreach reminder for colonoscopy screening (control), with an email with active choice to opt in or opt out of screening (active choice), or an active choice email plus a $100 incentive (financial incentive). Colonoscopy completion was evaluated at 3 months.…”
Section: N March 2014 the National Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…12 Organizational and leadership alignment on our CRC screening goal has contributed to our ability to double CRC screening rates in the first 5 years of our program. 12 In this issue of Gastroenterology, Mehta et al 13 at the University of Pennsylvania performed a randomized trial among 2245 employees of their institution comparing an email outreach reminder for colonoscopy screening (control), with an email with active choice to opt in or opt out of screening (active choice), or an active choice email plus a $100 incentive (financial incentive). Colonoscopy completion was evaluated at 3 months.…”
Section: N March 2014 the National Colorectal Cancermentioning
confidence: 99%
“…There was with no difference between the active choice and control arms. 13 The literature on financial incentives in CRC screening has been mixed. Modest $5 or $10 incentives have not shown a significant effect on improving CRC screening rates, but a 1 in 10 chance of winning $50 increased participation by nearly 20%.…”
Section: N March 2014 the National Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were randomly allocated to one of two groups, according to the incentive offer in their invitation letters: either (1) a single €10 ($12) incentive upon completion of screening, or (2) two €5 ($6) incentives offered at the beginning and at the end of screening. The former is the standard method employed in previous research, with a single incentive, offered conditional with completing the health procedure, whereas the latter tests the hypothesis of partitioned incentives.…”
Section: Methodsmentioning
confidence: 99%
“…Screening rates ranged between 34% and 37%, with no statistical differences between the groups. Mehta et al . recently reported that a $100 incentive increased colonoscopy rates by only 2% ( n = 2245).…”
Section: Introductionmentioning
confidence: 99%